Perception of the nursing in neonatal intensive care unit under the newborn’s dying process (Brazilian Journal of Health Research, 2022)
Introduction: An intensive care unit requires special care and the work of qualified nurses. Objectives: To know the experience of coping with nurses in the face of death and grief within a neonatal ICU and their coping strategies. Methods: This is a descriptive, qualitative study where the research subjects consisted of seven professionals from the nursing team who worked in a neonatal intensive care unit in a large hospital in the city of Piracicaba-SP. The data collection instrument was a semi-structured interview with a script of open questions, and the collected material was recorded and transcribed in full. Results: The grouping of similar Central Ideas resulted in seven Collective Subject Discourses that were grouped into three three categories: 1) difficulties in dealing with death; 2) the meaning of dignified death; and 3) coping strategies to experience death and grief. Conclusion: For most of the nurses interviewed, death inside the NICU generates a feeling of impotence and anguish. It is necessary for professionals working in the NICU to be specialists in this work environment, and for health institutions to offer psychological support so that their employees know how to deal with the team and family in the best possible way with this sad reality.
Keywords: Nurses; Intensive care neonatal; Death